(No) We, I, Myself and Them? - Christin Bolewski (2018)
This is an outcome of a practice-based research project that revisits concepts and contents of Eastern traditional art via contemporary digital visualisation technology. The Eastern concept of multi-perspective and the endless hand scroll are explored through digital filmmaking, video compositing and virtual camera, depths and particle systems and mixed with life recorded video footage. The video art animation is presented on wall-mounted flat screen displays as video painting and is an intercultural remediation, genre mix and remake of the ancient Chinese hand scroll Along the River During the Qingming Festival by the Song dynasty artist Zhang Zeduan capturing the daily life of people and the landscape of on old Chinese capital. This old master piece is adopted into a contemporary manner by using contemporary and historical documentary video footage of Tianamen Square in Beijing and presents excerpts from the poem “Massacre” of the Chinese author Liao Yiwu commenting on Tiananmen Square incidents in 1989 as a reflection on the conflicting relationship between the individual and society struggling between tradition and cultural progress and global influences.